2013
DOI: 10.1063/1.4821508
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of large-area 3D optical fishnet metamaterial by laser interference lithography

Abstract: Centimeter-scale 3D fishnet metamaterial with negative refractive index in the near infrared spectral range is demonstrated. The large-area fabrication is realized using a conventional laser interference lithography technique in combination with a tri-layer lift-off procedure. This method allows us to effectively achieve a centimeter-scale 3D fishnet structure with a pitch of 600 nm and five functional Ag/SiO2 bi-layers with a total thickness of 300 nm. The experimental transmission spectrum correlates well wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Similarly, fishnet NZIMs can be found operating at both the near-infrared region and the visible spectrum 16,29. The major drawback for the large area production of metamaterials nowadays is their cost since the commonly used lithographic techniques based on electron beam,22 laser interferometry20 or focused ion beam30 imply expensive and low-throughput processes. Even when using nanoimprinting or nanosphere lithography (NSL), most of the procedures still involve costly top-down deposition equipment such as electron beam evaporation18 or sputtering 31.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, fishnet NZIMs can be found operating at both the near-infrared region and the visible spectrum 16,29. The major drawback for the large area production of metamaterials nowadays is their cost since the commonly used lithographic techniques based on electron beam,22 laser interferometry20 or focused ion beam30 imply expensive and low-throughput processes. Even when using nanoimprinting or nanosphere lithography (NSL), most of the procedures still involve costly top-down deposition equipment such as electron beam evaporation18 or sputtering 31.…”
Section: Introductionmentioning
confidence: 99%
“…17,18 We have highlighted realizations of photonic crystals in the photovoltaic area 19,20 and of finite grating couplers 21 using this technique. A single exposure by LIL gives fringes with a spatial period K ¼ k=2 sinðhÞ, where k is the wavelength of the laser and h is the half-angle between the two interfering beams.…”
mentioning
confidence: 99%
“…The development of three-dimensional optical metamaterials (MMs) has been challenging due to the many physical and technological roadblocks that are encountered in their fabrication . One of the most widely investigated architectures, the negative-index fishnet MM, is also probably the most compatible with current nanofabrication tools because its making requires only a single step of electron-beam or laser lithography. , Recent articles have shown that fishnet MMs can also be fabricated with laser interference lithography or nanotransfer printing, enabling large-scale production with minimal efforts. Other useful approaches for fabricating 3D optical MMs include direct laser printing (which is especially suited for fabricating chiral structures, although the minimum feature size is limited by the wavelength used for writing) as well as self-assembled techniques, for example by using block copolymers and metal electrodeposition .…”
mentioning
confidence: 99%